Trust and growth revisited - Simplice Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2017)
The paper extends Breggren et al. (2008, EE) on "trust and growth: a shaky relationship" by incorporating recent developments in the trust-growth literature and using a robust methodological underpinning that accounts for the presence of outliers. The empirical evidence is based on 63 countries. Two main findings are established. First, the substantially documented positive trust-growth nexus is broadly confirmed. Second, when initial levels of growth come into play in determining the relationship, only the 25th quartile and 90th decile confirm the positive nexus. The results suggest that the trust-growth nexus cannot be generalized for all countries as some previous studies have concluded. Accordingly, trust-growth policies should be contingent on existing levels of development and tailored differently across rich and poor countries.
Keywords: A13; O40; Z13; 330; Trust; Growth; Conditional Effects